Surgical findings and outcomes after unilateral adrenalectomy for primary hyperaldosteronism in cats: a multi-institutional retrospective study. Issue 1 (January 2023) - Del Magno, Sara; Foglia, Armando; Rossanese, Matteo; Montinaro, Vincenzo; Cola, Veronica; Pisoni, Luciano; Rossetti, Diego; Cantatore, Matteo; De La Puerta, Benito; Nicoli, Stefano; Pisani, Guido; Collivignarelli, Francesco; et al.
Case series summary: Twenty-nine cats from different institutions with confirmed or highly suspected primary hyperaldosteronism treated by unilateral adrenalectomy were retrospectively included in this study. The most frequent clinical signs were lethargy (n = 20; 69%) and neck ventroflexion (n = 17; 59%). Hypokalaemia was present in all cats, creatinine kinase was elevated in 15 and hyperaldosteronism was documented in 24. Hypertension was frequently encountered (n = 24; 89%). Preoperative treatment included potassium supplementation (n = 19; 66%), spironolactone (n = 16; 55%) and amlodipine (n = 11; 38%). There were 13 adrenal masses on the right side, 15 on the left and, in one cat, no side was reported. The median adrenal mass size was 2 × 1.5 cm (range 1–4.6 × 0.4–3.8); vascular invasion was present in five cats, involving the caudal vena cava in four cats and the renal vein in one. Median duration of surgery was 57 mins. One major intraoperative complication (3%) was reported and consisted of haemorrhage during the removal of a neoplastic thrombus from the caudal vena cava. In 4/29 cats (14%), minor postoperative complications occurred and were treated medically. One fatal complication (3%) was observed, likely due to disseminated intravascular coagulation. The median duration of hospitalisation was 4 days; 97% of cats survived to discharge. The potassium level normalised in 24 cats within 3 months of surgery; hypertension resolved in 21/23 cats. Follow-up was available for 25 cats with a median survival of 1082 days. Death in the long-term follow-up was mainly related to worsening of comorbidities. Relevance and novel information: Adrenalectomy appears to be a safe and effective treatment with a high rate of survival and a low rate of major complications. Long-term medical treatment was not required.